2019
DOI: 10.11591/ijeecs.v13.i1.pp324-330
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristic of photovoltaic thermal collector with water-multiwalled carbon nanotube nanofluid flow

Abstract: Photovoltaic thermal (PVT) studies show promising results from utilizing waste heat under the PV module. Heat removal is essentially the base of a PVT collector. The heat absorption from the back of the PV module used for different purposes. Solar energy being collected are mostly turned into heat and needs to be extracted to maintain PV’s efficiency. The PVT collector works similar to a flat plate solar collector, except that the short wavelengths are converted into electricity and the remaining wavelengths i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The results of maximum power generated showed that it increased from 5.995 W to 7.384 W firstly and then dropped to 6.588 W. The reason was that the module did not withstand the converged radiation from the solar simulator and it can be seen due to a sudden decrease in maximum power produced as has been tabulated in Table 4. One of the reasons that led to this result is due to the high PV cell temperature due to increase in solar radiation which affected the performance of the solar panel [21].…”
Section: A Control System Response With Pole Placement Methodsmentioning
confidence: 99%
“…The results of maximum power generated showed that it increased from 5.995 W to 7.384 W firstly and then dropped to 6.588 W. The reason was that the module did not withstand the converged radiation from the solar simulator and it can be seen due to a sudden decrease in maximum power produced as has been tabulated in Table 4. One of the reasons that led to this result is due to the high PV cell temperature due to increase in solar radiation which affected the performance of the solar panel [21].…”
Section: A Control System Response With Pole Placement Methodsmentioning
confidence: 99%
“…They also learned this design has a lower pressure drop and uses up to 30% more efficient materials, reducing manufacturing costs. Furthermore, an experiment on a spiral rectangular tube absorber was conducted by Razali et al [107]. However, it was observed that the sharp-angle of this rectangular tube creates a significant pressure loss so that the maximum increase in power is obtained at a mass flow rate of 0.0255 kg/s.…”
Section: Spiralmentioning
confidence: 99%
“…These parts of Africa very seldom have access to electricity; thus, they cannot use a standard fridge [9][10][11]. The numerous improvements to renewable energytechnology, particularly solar energy harnessing and conversion into electrical energyby means of PV panels [12][13][14][15][16][17][18][19][20][21], brings about a good opportunity to arrst the grand challenge of electrical energy in rural areas. This being opportunity to solve not only the challenge of vaccine storage but extends to several other thermoelectric applications [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%